ISLAM BERKEMAJUAN DALAM JEJAK NABI DAN KIAI: ANALISIS PERBANDINGAN DAKWAH RASULULLAH SAW DAN KH. AHMAD DAHLAN - Rosad, Safiq; Rahmadi, Aris; Syukri, Muhammad (Institut Agama Islam Sahid (INAIS) Bogor, 2025)
This research explores the relevance of K.H. Ahmad Dahlan’s struggle and the founding of Muhammadiyah with the prophetic mission of Prophet Muhammad SAW, particularly in the context of Islamic reform, the liberation of the ummah, and the modernization of Islamic education. Muhammadiyah emerged as a progressive Islamic movement through an organized system, marking a shift from traditional religious authority centered on individual clerics to a more systematic and rational approach. Inspired by global Islamic reform movements and the Prophet’s method of building a da’wah community, K.H. Ahmad Dahlan rejected taqlid (blind following), superstitions, and secularism. Using a library research methodology, this study analyzes historical and conceptual connections that reflect the alignment between the Prophet’s strategy and Muhammadiyah’s ideological and practical framework. The findings reveal that Muhammadiyah consistently embodies the values of tawhid, ijtihad, mu’amalah dunyawiyah, and modern education as a form of holistic (kafah) Islamic implementation—following the prophetic legacy in establishing a just and progressive Islamic civilization.